2006
DOI: 10.12930/0271-9517-26.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Microskills: Advisor Behaviors that Improve Communication with Advisees

Abstract: In writing this article, we wanted to provide advisors practical means with which to optimize their relationships with advisees. First, we describe behavioral microskills that can be used by advisors to enhance advising sessions. Attending behaviors (eye contact, vocal cadence and tone, verbal tracking, body language) and listening skills (asking questions, observing, guiding discussion, reflecting feelings) are two core microskills that advisors can practice. Use of these microskills has been shown to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The limited research on the student-advisor relationship focuses predominantly on advisor attitudes and experiences (e.g., Allen and Smith 2008), suggested guidelines or behaviors for effective advising (e.g., Barbuto et al 2011;Barnett et al 2006), advising as a means to increase student retention (mostly among undergraduates; e.g., Heisserer and Parette 2002;Soria 2012, Tinto 1999 and advising relationships being important for professional development (e.g., Schlosser et al 2011). While these are essential topics, connections between the student-advisor relationship and graduate student wellbeing is also of critical value.…”
Section: Introductionmentioning
confidence: 99%
“…The limited research on the student-advisor relationship focuses predominantly on advisor attitudes and experiences (e.g., Allen and Smith 2008), suggested guidelines or behaviors for effective advising (e.g., Barbuto et al 2011;Barnett et al 2006), advising as a means to increase student retention (mostly among undergraduates; e.g., Heisserer and Parette 2002;Soria 2012, Tinto 1999 and advising relationships being important for professional development (e.g., Schlosser et al 2011). While these are essential topics, connections between the student-advisor relationship and graduate student wellbeing is also of critical value.…”
Section: Introductionmentioning
confidence: 99%
“…Rapport is defined as more than simply being civil to or respectful of one another. To like students as interesting people and be willing to engage in friendly, meaningful conversation, as advocated by Barnett et al (2006) and Yudof (2003), a deeper relationship must develop between advisor and advisee over the course of their advising conversations. The building of rapport in this context is likely influenced by the affective aspects of their communication.…”
Section: Discussionmentioning
confidence: 99%
“…Partially in response to student dissatisfaction expressed during the past 20 years with respect to academic advising (Habley & Crockett, 1988;Habley & Morales, 1998;Hanson & Huston, 1995), newer methods have emerged. For example, academic advisors have been called on to express certain advising competencies, such as teaching and observational abilities (Fiddler & Alicea, 1996), and more recently, approaches to the advisor-student relationship have embraced "liking" students as interesting people willing to engage in friendly, meaningful conversation (Barnett, Roach, & Smith, 2006;Yudof, 2003). This milieu provides an environment supporting the reemergence of the development-oriented paradigm expressed by Crookston (1972) and is consistent with advising as teaching-learning (Hemwall & Trachte, 2005;Uhlik, 2004).…”
mentioning
confidence: 99%
“…Kutze, van der Molen, and Born (2009) found that psychology students who were taught this method exhibited similar counseling behaviors, especially in terms of those associated with empathy. In a small study of academic advisors, Bartnett, Roach, and Smith (2006) found that learning the microskills associated with attending behavior strengthened advisor-advisee relationships. McAuliffe and Lovell (2006) used the microskills model with beginning students in a counseling program, and also found an increase in the use of an empathic approach, an important determinant of effectiveness in an encounter.…”
Section: The Microskills Modelmentioning
confidence: 99%